Achieving a Healthy and Prosperous Quality of Life through a Low-Carbon Lifestyle - Hamidah, Ida; Hasanah, Lilik; Anggraeni, Leni (Jurnal Abmas Negeri (JAGRI), 2025)
Migrant workers often face challenges in maintaining a healthy quality of life due to various factors, including unsupportive work environments, lack of access to healthcare facilities, and unhealthy lifestyles. In addition, the increase in carbon emissions related to human activities has become a global issue that requires serious attention. Combining efforts to improve quality of life with steps to reduce carbon emissions can help achieve the SDGs, namely good health and well-being, clean water and sanitation, affordable and clean energy, and climate action. This Community Service Program (PkM) aims to: (1) improve healthy living quality through education and implementation of healthy lifestyles, (2) raise awareness about the importance of maintaining health and the environment simultaneously, and (3) reduce the carbon footprint by promoting low-carbon lifestyles. The method used is an integrated approach that involves four stages: (1) education and training through seminars and workshops, (2) facilitating access to healthcare facilities, (3) campaigns and mentoring to encourage lifestyle changes, and (4) evaluation and monitoring to measure the program's impact. The results of this program show that migrant workers have high awareness in adopting healthy and low-carbon lifestyles, although improvements are still needed in some areas such as recycling and the selection of low-carbon products. In conclusion, this program can make a real contribution to improving the quality of life of migrant workers while reducing negative environmental impacts. Recommendations for future programs include strengthening recycling campaigns and increasing awareness of low-carbon product consumption.